Effect Of Various Additives On The Properties Of Poly(L-Lactic Acid)/Poly(Butylene Succinate-Col- Lactate) Blend - Chou, Pui May (2011)
Polymer blends of poly(L-lactic acid) (PLLA) and poly(butylene succinate-co-Llactate) (PBSL) at various blending ratios were prepared through melt mixing method. The blending of PLLA with PBSL resulted in an improvement in the toughness and thermal stability of the PLLA blend. However, flexural strength and modulus decreased with the increase in PBSL content. Annealing was conducted after the optimum blending ratio was determined. Analysis on the annealing revealed that the degree of crystallinity and flexural modulus were enhanced with increasing annealing time. Next, poly(ethylene adipate) (PEA) and poly(tetramethylene ether glycol) (PTMEG) were added as compatibilizers to the PLLA/PBSL blend.